Industrial IoT technologies and applications : second EAI International Conference, Industrial IoT 2017, Wuhu, China, March 25-26, 2017, Proceedings /: second EAI International Conference, Industrial IoT 2017, Wuhu, China, March 25-26, 2017, Proceedings. (2017) - Unknown
No abstract available